Computer literacy and job performance among Administrative Assistants in Kuching North City Hall (DBKU) - Chee, Kin Siong (2003)
The purpose of this study was to describe the computer literacy and job performance levels of the administrative assistants in Kuching North City Hall (DBKU). This study also attempted to determine if there was a relationship between computer literacy and job performance. In addition, this study also investigate if there were differences in computer literacy and job performance levels based on the administrative assistant's age, number of computer course attended, amount of computer experience and accessibility to office computers.